Aplicação da tabela de vida das culturas às pragas de Phaseolus vulgaris L. em quatro n´íveis e adubação: I. Em áreas de alta fertilidade - M C Della Lucia, Terezinha; Chandler, Leland; W Dias Casali, Vicente; Domingos Galvão, José; H Freire, José Alberto; M da Costa, Liovando (Revista Ceres, 2025)
Two plantings of beans (Phaseolus vulgaris L., cv ‘Ricobaio’) were made during the agricultural year of 1979-1980, one during the rainy season and one during the dry, in the high-fertility experimental area of the Department of Agronomy, Federal University of Vicosa. The objective of the research was to evaluate the relationships between fertility levels and insect pest damage.